Global report on preterm birth and stillbirth (5 of 7): advocacy barriers and opportunities - Rubens Craig E; Zaentz Rachel; Fajon Anne-Véronique; Sather Megan (BMC, 2010)
Abstract Background Efforts to achieve the Millennium Development Goals (MDGs) to improve maternal and child health can be accelerated by addressing preterm birth and stillbirth. However, most global health stakeholders are unaware of the inextricable connections of these adverse pregnancy outcomes to maternal, newborn and child health (MNCH). Improved visibility of preterm births and stillbirths will help fuel investments and strengthen commitments in the discovery, development and delivery of low-cost solutions globally. This article addresses potential barriers and opportunities to increasing global awareness and understanding. Methods Qualitative research was conducted to analyze current knowledge, attitudes and commitments toward preterm birth and stillbirth; identify advocacy challenges; and learn more about examples of programs that successfully advocate for research and appropriate interventions. Forty-one individuals from 14 countries on six continents were interviewed. They included maternal, newborn, and child health advocates and implementers, United Nations agency representatives, policymakers, researchers, and private and government donors. Results A common recognition of three advocacy challenges with regard to preterm birth and stillbirth emerged from these interviews: (1) lack of data about the magnitude and impact; (2) lack of awareness and understanding; and (3) lack of low-cost, effective and scalable interventions. Participants also identified advocacy opportunities. The first of these opportunities involves linking preterm birth and stillbirth to the MDGs, adding these outcomes to broader global health discussions and advocacy efforts, and presenting a united voice among advocates in the context of broader MNCH issues when addressing preterm birth and stillbirth. Another key opportunity is putting a human face to these tragedies-such as a parent who can speak to the personal impact on the family. Lastly, several interviewees suggested identifying and engaging champions to garner additional visibility and strengthen efforts. Ideal champions will work collaboratively with these and other maternal, newborn and child health issues. Conclusion: Advocacy efforts to add preterm births and stillbirths to broader MNCH goals, such as the MDGs, and to identify champions for these issues, will accelerate interdisciplinary efforts to reduce these adverse outcomes. The next article in this report presents an overview of related ethical considerations.